2021
DOI: 10.21037/atm-21-5598
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of multitarget indirect enzyme-linked immunoassay assay for detection of tuberculosis antibody

Abstract: Background: Diagnosis of tuberculosis (TB) is still difficult. The development of rapid and sensitive laboratory tools for the diagnosis of tuberculosis is a priority. This study aimed to develop an indirect enzyme-linked immunoassay (ELISA) assay for detection of TB antibody and explore its diagnostic value in patients with pulmonary tuberculosis (PTB) via a multi-center clinical evaluation. Methods:The specific antigen, fusion antigen, and specific antibody peptide were obtained using molecular cloning and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Over the past 2 decades, evidence from prior studies indicates that several promising candidates’ immunogenic antigens have been identified and the adjustment of existing serological tests with these antigens is practicable [ 14–17 ]. A large number of commercial antibody diagnosis tests have been developed and evaluated [ 13 , 18 , 19 ], however, the diagnostic accuracy of commercial immunological tests based on specific antigen and antibody reactions varies widely, and no large-scale clinical estimation of this diagnostic approach has been performed in clinical practice. Thus, we aimed to evaluate the clinical utilization of existing M. tuberculosis 16kD, 38kD, LAM, CFP-10, and Rv1636 antigens, and the bacteriological specificity of each antigen in patients with suspected active tuberculosis in The Fourth People’s Hospital of Nanning.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 2 decades, evidence from prior studies indicates that several promising candidates’ immunogenic antigens have been identified and the adjustment of existing serological tests with these antigens is practicable [ 14–17 ]. A large number of commercial antibody diagnosis tests have been developed and evaluated [ 13 , 18 , 19 ], however, the diagnostic accuracy of commercial immunological tests based on specific antigen and antibody reactions varies widely, and no large-scale clinical estimation of this diagnostic approach has been performed in clinical practice. Thus, we aimed to evaluate the clinical utilization of existing M. tuberculosis 16kD, 38kD, LAM, CFP-10, and Rv1636 antigens, and the bacteriological specificity of each antigen in patients with suspected active tuberculosis in The Fourth People’s Hospital of Nanning.…”
Section: Introductionmentioning
confidence: 99%